Centella Asiatica Ethanolic Extracts Reduces Interleukin-1β Expression in the Gastric Mucosa of Indomethacin-Induced Ulcer Rats - Fatimah Nur Fitriani; Made Dinda Pratiwi (GLOBAL HEALTH SCIENCE GROUP, 2026)
Gastric ulcers are a common gastrointestinal disorder affecting millions worldwide, with complications contributing to high hospitalisation rates. Pro-inflammatory cytokines, particularly IL-1β, play a key role in the inflammatory response and ulcer development. To evaluate the anti-inflammatory effect of Centella asiatica ethanolic extract (CAEE) on indomethacin-induced gastric ulcers in rats, focusing on IL-1β expression. An experimental study was conducted on 18 adult male Wistar rats divided into six groups: negative control (NC), positive controls (PC1 for 24 hours and PC8 for 8 days), and three treatment groups receiving CAEE at 100, 200, and 400 mg/kgBW (T1–T3). Gastric ulcers were induced with indomethacin (30 mg/kgBW), followed by seven days of CAEE administration. Gastric tissue was evaluated histologically using hematoxylin–eosin staining and immunohistochemically for IL-1β expression. Quantitative analysis was performed with ImageJ, and data were statistically tested using one-way ANOVA followed by Tukey’s post hoc test. Results:Indomethacin significantly increased IL-1β expression in the gastric mucosa (p=0.000). CAEE at 100, 200, and 400 mg/kgBW significantly reduced IL-1β expression compared with the PC8 group (p<0.05), with the strongest suppression at 400 mg/kgBW. Conclusions: CAEE demonstrates a dose-dependent anti-inflammatory effect by suppressing IL-1β expression, suggesting its therapeutic potential in gastric ulcer management.